Rutaecarpine Inhibits U87 Glioblastoma Cell Migration by Activating the Aryl Hydrocarbon Receptor Signaling Pathway - Liu, Yiyun; Chen, Yangsheng; Zhu, Ruihong; Xu, Li; Xie, Heidi Qunhui; Zhao, Bin (Frontiers in Molecular Neuroscience, 2021)
Glioblastoma is the most frequent and aggressive primary astrocytoma in adults. The high migration ability of the tumor cells is an important reason for the high recurrence rate and poor prognosis of glioblastoma. Recently, emerging evidence has shown that the migration ability of glioblastoma cell was inhibited upon the activation of aryl hydrocarbon receptor (AhR), suggesting potential anti-tumor effects of AhR agonists. Rutaecarpine is a natural compound with potential tumor therapeutic effects which can possibly bind to AhR. However, its effect on the migration of glioblastoma is unclear. Therefore, we aim to explore the effects of rutaecarpine on the migration of human glioblastoma cells U87 and the involvements of the AhR signaling pathway. The results showed that: (i) compared with other structural related alkaloids, like evodiamine and dehydroevodiamine, rutaecarpine was a more potent AhR activator, and has stronger inhibitory effect on the glioblastoma cell migration; (ii) rutaecarpine decreased the migration ability of U87 cells in an AhR-dependent manner; (iii) AhR mediated the expression of a tumor suppressor interleukin 24 (IL24) induced by rutaecarpine, and AhR-IL24 axis was involved in the anti-migratory effects of rutaecarpine on the glioblastoma. Besides IL24, other candidate AhR downstream genes both associated with cancer and migration were proposed to participate in the migration regulation of rutaecarpine by RNA-Seq and bioinformatic analysis. These data indicate that rutaecarpine is a naturally-derived AhR agonist that could inhibit the migration of U87 human glioblastoma cells mostly via the AhR-IL24 axis.